Systematic Study of the Oxidation of Methane Using Supported Gold Palladium Nanoparticles Under Mild Aqueous Conditions - Mohd Hasbi, Ab. Rahim; Forde, Michael M.; Hammond, Ceri; Jenkins, Robert L.; Dimitratos, Nikolaos; Lopez-Sanchez, Jose Antonio; Carley, Albert F.; Taylor, Stuart H.; Willock, David J.; Hutchings, Graham J. (Springer-Verlag, 2013)
The oxidation of methane using hydrogen peroxide has been studied using supported gold palladium catalysts prepared using the incipient wetness technique. The effect of reaction conditions and catalyst parameters has been investigated. The supported gold palladium nanoparticles produce methyl hydroperoxide as the primary reaction product which is subsequently converted to methanol with high selectivity, ca. 40–70 %. The selectivity to methanol is influenced by the oxidation state the palladium component of the catalyst. In contrast to homogeneous gold and palladium catalysts the heterogeneous gold palladium nanoalloys are reusable and affords high oxygenate selectivity (ca. 90 %).